2012
DOI: 10.1136/vr.100680
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus enteritis in Eurasian badgers (Meles meles)

Abstract: However, no viral enteropathogens have been confirmed in Great Britain or throughout the range of the Eurasian badger. Histopathological findings suggestive of parvovirus enteritis have been seen in cases of diarrhoea in captive, hand-reared badgers. However, the presence of parvovirus has never been confirmed by laboratory means in these cases (Mullineaux 2003). Parvovirus infection has also been suspected as the cause of myocarditis in a Eurasian badger (Burtscher and Url 2007). This again was based only on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The investigation of the cause of clinical illness in wildlife casualties may lead to the identification of novel pathogens not previously described in that species, such as those associated with enteric disease in European badger ( Meles meles ) cubs (Barlow et al. , ) and causing Tyzzer's disease in a rehabilitated European otter ( Lutra lutra ) (Simpson et al. ).…”
Section: Rationale For Treatment and Rehabilitation Of Wildlife Casuamentioning
confidence: 99%
“…The investigation of the cause of clinical illness in wildlife casualties may lead to the identification of novel pathogens not previously described in that species, such as those associated with enteric disease in European badger ( Meles meles ) cubs (Barlow et al. , ) and causing Tyzzer's disease in a rehabilitated European otter ( Lutra lutra ) (Simpson et al. ).…”
Section: Rationale For Treatment and Rehabilitation Of Wildlife Casuamentioning
confidence: 99%
“…Of these, the viruses from coyote, gray wolf, and striped skunk are only CPV-like, as are most raccoon parvoviruses. However, any such phylogenetic rule is clearly a weak one because viruses from bobcats and pumas (suborder Feliformia) are either exclusively or predominantly CPV-like, and FPV-like viruses were recently discovered in Eurasian badgers (8), a cani- Early studies suggested that CPV in dogs was directly derived from an FPV in a domestic cat (4,16). However, the diverse range of parvoviruses in other carnivore species means that is no longer necessary to think that cats must be the source of the virus that emerged in dogs in the late 1970s.…”
mentioning
confidence: 99%
“…A variety of host species other than domestic cats and dogs harbor closely related parvoviruses, and it has become increasingly apparent that nondomestic animals are commonly infected, even though little disease is observed in many cases (8)(9)(10)(11)(12). However, those parvoviruses previously detected in a variety of other species, including many different large cats, raccoons, raccoon dogs, arctic foxes, and mink, often represent opportunistic samples obtained from animals in artificial settings such as zoos or fur farms (13)(14)(15), with the majority of these viruses falling into a single FPV-like clade distinct from CPV in dogs (4,16).…”
mentioning
confidence: 99%
“…Another interesting finding of the present report is that the only two parvovirus strains detected in wildlife were both CPV‐2a. While FPLV and all the three CPV variants have been detected in wild carnivores in the USA (Allison et al., ), in Europe, only FPLV and CPV‐2b have been proven to circulate in wildlife (Battilani et al., ; Steinel et al., ; Barlow et al., ; Duarte et al., ). In some instances, the lack of sequence analyses of the VP2 protein gene or of the sophisticated molecular tools, such as MGB probe assays, prevented any definitive characterization of the parvoviruses circulating in wild carnivores (Martinello et al., ; Burtscher and Url, ; Duarte et al., ).…”
Section: Discussionmentioning
confidence: 99%